Sequential Analysis of Binding and Neutralizing Antibody in COVID-19 Convalescent Patients at 14 Months After SARS-CoV-2 Infection - Rosati, Margherita; Terpos, Evangelos; Ntanasis-Stathopoulos, Ioannis; Agarwal, Mahesh; Bear, Jenifer; Burns, Robert; Hu, Xintao; Korompoki, Eleni; Donohue, Duncan; Venzon, David J.; Dimopoulos, Meletios-Athanasios; Pavlakis, George N.; et al. (Frontiers in Immunology, 2021)
Durability of SARS-CoV-2 Spike antibody responses after infection provides information relevant to understanding protection against COVID-19 in humans. We report the results of a sequential evaluation of anti-SARS-CoV-2 antibodies in convalescent patients with a median follow-up of 14 months (range 12.4-15.4) post first symptom onset. We report persistence of antibodies for all four specificities tested [Spike, Spike Receptor Binding Domain (Spike-RBD), Nucleocapsid, Nucleocapsid RNA Binding Domain (N-RBD)]. Anti-Spike antibodies persist better than anti-Nucleocapsid antibodies. The durability analysis supports a bi-phasic antibody decay with longer half-lives of antibodies after 6 months and antibody persistence for up to 14 months. Patients infected with the Wuhan (WA1) strain maintained strong cross-reactive recognition of Alpha and Delta Spike-RBD but significantly reduced binding to Beta and Mu Spike-RBD. Sixty percent of convalescent patients with detectable WA1-specific NAb also showed strong neutralization of the Delta variant, the prevalent strain of the present pandemic. These data show that convalescent patients maintain functional antibody responses for more than one year after infection, suggesting a strong long-lasting response after symptomatic disease that may offer a prolonged protection against re-infection. One patient from this cohort showed strong increase of both Spike and Nucleocapsid antibodies at 14 months postinfection indicating SARS-CoV-2 re-exposure. These antibodies showed stronger cross-reactivity to a panel of Spike-RBD including Beta, Delta and Mu and neutralization of a panel of Spike variants including Beta and Gamma. This patient provides an example of strong anti-Spike recall immunity able to control infection at an asymptomatic level. Together, the antibodies from SARS-CoV-2 convalescent patients persist over 14 months and continue to maintain cross-reactivity to the current variants of concern and show strong functional properties.